2011
DOI: 10.1093/rpd/ncr226
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of 50 Hz magnetic fields in apartment buildings with indoor transformer stations

Abstract: Twenty-four hour measurements of 50 Hz magnetic fields (MFs) in apartment buildings containing transformer stations have been performed. The apartments were classified into four types, according to their location relative to the transformer room. Temporal correlation coefficients between the MF in various apartments, as well as between MF and transformer load curves, were calculated. It was found that, in addition to their high average MF, the apartments located right above the transformer room also exhibit un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…The number of spaces where it has been measured is indicated, and finally the average value of the measurements made in the bed or beds of the most affected spaces are also presented. Our measurements are within the order of magnitude of the measurements carried out in Finland, Switzerland, Hungary, Israel, Bulgaria, and The Netherlands [10][11][12][13][14][15][16][17][18], in the framework of the TransExpo Project [15]. The average of the average values gives us an average value of 0.4 µT for the dwellings above or adjacent to the TS.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…The number of spaces where it has been measured is indicated, and finally the average value of the measurements made in the bed or beds of the most affected spaces are also presented. Our measurements are within the order of magnitude of the measurements carried out in Finland, Switzerland, Hungary, Israel, Bulgaria, and The Netherlands [10][11][12][13][14][15][16][17][18], in the framework of the TransExpo Project [15]. The average of the average values gives us an average value of 0.4 µT for the dwellings above or adjacent to the TS.…”
Section: Resultssupporting
confidence: 52%
“…This is important in order to have some assurance that the measure being taken has its source in the TS, and not in the wiring of the house itself. These circumstances are not obvious in the previous works [10][11][12][13][14][15][16][17][18]. Also, when the successive averages are carried out, the values obtained are smoothed out and do not appear to be so high; however, they are high in some areas where values of 2-20 µT were reached.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Yitzhak and colleagues performed a 24-h measurement of 50 Hz magnetic fields in apartments of buildings containing transformer stations. They found that average magnetic field in apartments above the transformer room were 0.33 µT, significantly stronger than those measured in apartments positioned at greater distances from the transformer station (from 0.06 to 0.11 µT) [ 31 ].…”
Section: Exposure Assessment and Monitoring In Europementioning
confidence: 99%